Association of vitamin D deficiency with an increased risk of late-onset neonatal sepsis. (3rd July 2018) - Dhandai, Rajeshwari; Jajoo, Mamta; Singh, Amitabh; Mandal, Anirban; Jain, Rahul
Abstract: Background: Vitamin D deficiency in mothers and neonates is being recognised increasingly as a leading cause of many adverse health effects in the newborn infant, including sepsis. Methods: A prospective observational study was conducted at a tertiary care Paediatric teaching hospital in northern India to assess vitamin D deficiency as a possible risk factor for late-onset sepsis (LOS) in term and late preterm neonates and also to examine the correlation between maternal and infant vitamin D levels during the neonatal period. Late-onset sepsis (LOS) was defined as the development of signs and symptoms of severe sepsis after 72 h of life and a positive sepsis screen. All term and late preterm neonates admitted with LOS between September 2015 and February 2016 who had not been previously admitted for >48 h and had not been prescribed antibiotics or vitamin D were included in the study. Matched controls were recruited from otherwise healthy neonates admitted with physiological hyperbilirubinaemia. Serum 25(OH) vitamin D was assessed in neonates in both groups and their mothers. Results: A total of 421 neonates were admitted to the neonatal intensive care unit during the study period, 120 of whom satisfied the inclusion criteria, and 60 were recruited as cases. Sixty neonates were recruited as controls who were similar in gender, gestational age, age at admission and anthropometry. The study group had significantly lower mean (SD) vitamin D levels [15.37 ng/ml (10.0)] than the control group [21.37 ng/ml (9.53)] ( p  = 0.001). The odds ratio was 1.7 (95% CI 0.52–5.51) for LOS in vitamin D-deficient neonates. Mothers of septic neonates also had significantly lower mean (SD) vitamin D levels [17.87 (11.89)] than the mothers of non-septic neonates [23.65 ng/ml (9.55)] ( p  = 0.004). Maternal vitamin D levels strongly correlated to neonatal vitamin D levels in both groups. Conclusion: Neonates with vitamin D deficiency are at greater risk of LOS than those with sufficient vitamin D levels.